How Do Prospective Teachers Understand Educational Research?. Issue 1 (11th November 2020) - Perines, Haylen; Ion, Georgeta
Abstract: Despite the benefits that research offers for the development of teaching practice, prospective teachers appear to be reluctant toward research. A variety of predictors of research use have been analyzed and the prospective teachers' conceptions of research appears as one of the most powerful one. This research aims to explore the prospective teachers' conception of educational research. A qualitative study based on six focus groups was carried out with students from different teacher education programs in a Chilean public university (N = 48). Findings show that students conceive research as a useful tool to solve educational problems and that prospective teachers' conceptions are influenced by the methodology used in some courses of the teaching program and the teacher's approach. Paper lead to understand how prospective teachers conception toward research can be shaped by the study programs.